The Household Enterprise Sector in Tanzania : Why It Matters and Who Cares - Kweka, Josaphat; Fox, Louise (2012)
The household enterprise sector has a significant role in the Tanzanian economy. It employs a larger share of the urban labor force than wage employment, and is increasingly seen as an alternative to agriculture as a source of additional income for rural and urban households. The sector is uniquely placed within the informal sector, where it represents both conditions of informal employment and informal enterprise. This paper presents a case study on Tanzania using a mixed approach by combining both quantitative and qualitative analysis to examine the important role of household enterprises in the labor force of Tanzania, and to identify key factors that influence their productivity. Household enterprise owners are similar to typical labor force participants although primary education appears to be the minimum qualification for household enterprise operators to be successful. Access to location matters -- good, secure location in a marketplace or industrial cluster raises earnings - and access to transport and electricity is found to have a significant effect on earnings as well. In large urban areas, the biggest constraint faced by household enterprises is the lack of access to secure workspace to run the small business. Although lack of credit is a problem across all enterprises in Tanzania, household enterprises are more vulnerable because they are largely left out of the financial sector either as savers or borrowers. Although HEs are part of the livelihood strategies of over half of households in Tanzania, they are ignored in the current development policy frameworks, which emphasize formalization, not productivity. Tanzania has a large number of programs and projects for informal enterprises, but there is no set of policies and program interventions targeted at the household enterprise sector. This gap exacerbates the vulnerability of household enterprises, and reduces their productivity.